The epidemiology of measles in Tianjin, China, 2005–2014. Issue 46 (17th November 2015) - Wang, Xiexiu; Boulton, Matthew L.; Montgomery, JoLynn P.; Carlson, Bradley; Zhang, Ying; Gillespie, Brenda; Wagner, Abram L.; Ding, Yaxing; Luo, Xiaoyan; Hong, Tian
Highlights: Despite a gradual decline in reported measles cases, outbreaks continue to occur. Males were more likely than females to acquire measles, especially among very young children. Non-locals are contributing to measles transmission but the proportion of non-local cases is actually smaller than the proportion of the population they represent. Although SIAs successfully reduce cases in the immediate aftermath, numbers rebound 1–3 years following these resource intensive interventions. Abstract: Background: Measles incidence in China has declined over the last decade and elimination is targeted by 2020. Despite increases in routine immunization services and supplementary immunization activities (SIAs), periodic outbreaks continue to occur. In this paper, we examine measles epidemiology during 2005–2014 in Tianjin, China. Methods: Measles case data were extracted from a web-based communicable disease surveillance system. We examined the socio-demographic characteristics of measles case patients, including age, sex, urbanicity, residency status, and vaccination history. Demographic characteristics of cases were compared with the general population. Results: From January 1, 2005 to December 31, 2014, 12, 466 measles cases in Tianjin were reported. Among the cases, 7179 (57.6%) were male and 5287 (42.4%) were female. Over time, more cases occurred in adults, and for the 2711 cases in 2014, the majority were either infants <1 year (558, 20.58%) or adults ≥20 years (2043, 75.36%). Municipal-wide SIAs in Tianjin occurred in 2008 and 2010 with reduction in measles cases the following year for both (189 cases in 2009, and 37 cases in 2011). The number of cases rebounded to pre-SIA levels or higher within 1–3 years following each SIA: 1990 cases in 2010 and 2711 cases in 2014. Vaccination status was reported as "none" or "unknown" for 84% of all reported measles cases. Conclusions: Despite the general decline in cases, measles outbreaks continue to occur. Although the SIAs reduce numbers in their immediate aftermath, case counts rebound 1–3 years after the intervention. Continued monitoring of cases through disease surveillance activities accompanied by targeted immunization activities, including to adults, can help ensure progress toward elimination.